2015
DOI: 10.1590/0103-8478cr20140716
|View full text |Cite
|
Sign up to set email alerts
|

Dinâmica química, microbiológica e física da silagem de farelo úmido de glúten de milho

Abstract: RESUMO Objetivou-se avaliar aspectos físico-químicos e microbiológicos do farelo úmido de glúten de milho (FUGM) em função do tempo de ensilagem. O FUGM foi avaliado em silos experimentais e, nos dias um, três, sete, 14, 21, 28 46.54 and 49.05%; 0.96 and 1.71%;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
4
0
6
Order By: Relevance
“…Working with wet corn gluten bran, França et al (2015) observed that a longer ensiling period reduced the yeast and fungus counts, decreasing linearly from 7.2 to 5.5 log UFC g -1 of silage between 1 and 42 days of ensiling, due to the reduction of the concentration of oxygen in the silo. This is because the counts of fungi and yeasts during the first 8 days of silage are related to the epiphytic population in the material to be ensiled (Ávila, Bravo Martins, & Schwan, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Working with wet corn gluten bran, França et al (2015) observed that a longer ensiling period reduced the yeast and fungus counts, decreasing linearly from 7.2 to 5.5 log UFC g -1 of silage between 1 and 42 days of ensiling, due to the reduction of the concentration of oxygen in the silo. This is because the counts of fungi and yeasts during the first 8 days of silage are related to the epiphytic population in the material to be ensiled (Ávila, Bravo Martins, & Schwan, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Para minimizar as perdas por efluente, é importante que o teor de matéria seca seja correto, ou seja, no momento da ensilagem a planta deve ter em média de 35% de MS. A presença de umidade aumenta a produção de efluente, e o processo de ensilagem, desde a forma de colheita, processamento, estádio de maturação da planta, dentre outros, contribuem para a produção de efluente. Uma maneira de evitar as perdas por efluente é realizar a murcha na planta antes de ensilar, para que os nutrientes não lixiviem (França et al, 2014).…”
Section: Perda Por Efluenteunclassified
“…In addition, this co-product is produced in large amounts to reduce costs. Also, its storage does not involve any specific technique and is usually made by covering tall piles with plastic (FRANÇA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%